Correction to: Preliminary Insight into the Antifungal and Anti-melanogenic Potential of a Xanthenone-based Hit Compound: In Vitro and In Vivo Zebrafish Evaluation - Amirah Hani Ramli; PuAuthorNamejali Swain; E. H. T. Thulshan Jayathilaka; Mawalle Kankanamge Hasitha Madhawa Dias; Muhammad Syafiq Akmal Mohd Fahmi; Emilia Abdul Malek; Yaya Rukayadi; Kok Wai Lam; Yee Seng Tan; Chien Ing Yeo; Cheol-Hee Kim; Mahanama De Zoysa; et al. (Journal of Pharmaceutical Innovation, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Baseline Assessment of Coral Reef Condition, Diversity and Disease Prevalence in Darvel Bay, Northeastern Borneo - Aiman Azseri; Nur Angelie Agnezara Roger; Zepri Abdul Muhaimin; Mazni Muhammad Addin; Khairul Hisham Hariz; Siti Nur Hazwani Oslan; Khodzori Fikri Akmal (Thalassas: An International Journal of Marine Sciences, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

Preliminary Insight into the Antifungal and Anti-melanogenic Potential of a Xanthenone-based Hit Compound: In Vitro and In Vivo Zebrafish Evaluation - Amirah Hani Ramli; PuAuthorNamejali Swain; E. H. T. Thulshan Jayathilaka; Mawalle Kankanamge Hasitha Madhawa Dias; Muhammad Syafiq Akmal Mohd Fahmi; Emilia Abdul Malek; Yaya Rukayadi; Kok Wai Lam; Yee Seng Tan; Chien Ing Yeo; Cheol-Hee Kim; Mahanama De Zoysa; et al. (Journal of Pharmaceutical Innovation, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

Integrated Bioinformatics and Network Analysis Identifies Key Molecular Targets and Hub Genes in Zika Virus-induced Neuroinflammation - Akmal Zubair; Muhammad Ali; Adel Qlayel Alkhedaide (Journal of Molecular Neuroscience, 2026)

Biodegradation of plastics by the phosphorus-solubilising cyanobacterium Chroococcus sp. - Dani Wijaya; Japareng Lalung; Syahidah Akmal Muhammad; Peter Convey; Jebrel Abdeljawad Rashd; Law Heng Chuan; Andi Kurniawan; Nurul Huda (Journal of Applied Phycology, 2026)
Plastics often contain additives such as flame retardants, plasticisers, and stabilisers, with phosphorus-based compounds playing a key role in microbial interactions. Most previous studies have focused on heterotrophic microbes targeting carbon backbones, but their degradation efficiency remains limited. This study examined the phosphorus-solubilising ability of autotrophic cyanobacteria carrying the phoD gene to weaken polypropylene (PP) and polyethylene terephthalate (PET). Plastic samples collected from the Aquatic Research Complex fishpond at Universiti Sains Malaysia were incubated with isolates and analysed using NBRIP medium, molybdenum blue assay, UV–Vis, FTIR, SEM, and tensile strength testing over 61 days. Of the five strains isolated, Chroococcus sp. solubilised phosphorus from both PP and PET, releasing phosphorus into the medium and reducing plastic surface phosphorus. Treated plastics exhibited surface roughness, reduced dry mass, and significant tensile strength loss. This is the first report of photosynthetic cyanobacteria promoting plastic degradation via phosphorus scavenging.

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Biotechnological and nutraceutical evaluation of Boehmeria virgata root extract: Phytochemical profiling, antidiabetic bioactivity, and safety assessment - Haeria Doloking; Andi Andriani Musfar; Rahmi Fitri Lestari Jamal; Riska Yuniarti; Ainun Sakinah; Fitri Sea Febriani; Akmal Zulfi; Arif Setiawansyah; Muhammad Ikhlas Arsul; Alwiyah Nur Syarif; Muhammad Ikhwan Arsul (Biocatalysis and Agricultural Biotechnology, 2026)

Retraction Note: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2026)

Deciphering water scarcity footprint of auxiliary paddy irrigation via Available Water Remaining (AWARE)-LCA model for sustainable groundwater infrastructure - Naseem Akhtar; Abdulghani Essyah Musbah Swesi; Syahidah Akmal Muhammad; Muhammad Izzuddin Syakir; Raed Sameeh Raja Hussain; Pahmi Husain; Ateyah Alzahrani; Anwar Ulla Khan; Ahmad Alghamdi (Environmental Monitoring and Assessment, 2026)

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

Ecological Niche Overlap and Environmental Associations Among Species of the Morchella (Morchellaceae, Pezizomycotina) From P.R. China - Akmal Muhammad; Yinglian Deng; Syed Amir Manzoor; Changlin (Charlie) Zhao (New Zealand Journal of Botany, 2026)
Morchella species, economically significant edible fungi, are affected by numerous environmental factors; however, details concerning their ecological niche are poorly understood. Consequently, this study aims to fill this deficiency by applying a modeling approach to the fundamental niche of the Morchella genus, incorporating species from the elata and esculenta clades. In this work, we examined the distribution patterns of Morchella species in relation to significant environmental factors. The MaxEnt algorithm was utilized to conclude habitat validity. The environmental variables incorporated into the final models comprised isothermality, temperature seasonality, maximum temperature of the warmest month, mean temperature of the warmest quarter, precipitation of the wettest month, precipitation seasonality, slope, and aspect. The PCA‐env analysis revealed that the first two axes accounted for 69.55% of the overall variation in climatic conditions across the ranges of the two clades (PC1 = 41.36% and PC2 = 28.19%). An analysis and comparison of the climatic space engaged by the two primary clades, along with their overlap, were conducted. These findings emphasized the utility of ecological niche modeling for understanding how climatic conditions can influence the dispersal of Morchella clades. These results aid in formulating enhanced conservation strategies and in informed decision‐making across different ecosystems. It is essential to adopt a holistic approach to ecological modeling to foster sustainable conservation, evaluate diversity, and manage the valuable Morchella resources.

Solvent-selective extraction of Syzygium polyanthum bioactives for tailored polyvinyl alcohol composites: A lignocellulose-derived approach toward biorefinery-based functional materials - Dieter Rahmadiawan; Akmal; Hairul Abral; Muhammad Adlan Azka; S.M. Sapuan; Kadriadi; Dian Handayani; Dilla Ghania Putri; Upik Tadzkia Khairani; Ahmad Zikri; Shih-Chen Shi (Biomass and Bioenergy, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

Unlocking the role of transcription activator-like effector nuclease (TALENs) and zinc finger nuclease (ZFN) in the treatment of HIV - Akmal Zubair; Muhammad Ali; Faisal Ahmad; Saed Ayidh Althobaiti (Molecular Biology Reports, 2025)

Mechanisms of S-phase arrest and mitochondrial dysfunction in complex III by DHODH inhibitors in tumorigenic TNBC cells - Muhammad Aiman Akmal Shahhiran; Mohamad Fairus Abdul Kadir; Nurshamimi Nor Rashid; Puteri Shafinaz Abdul-Rahman; Shatrah Othman (Histochemistry and Cell Biology, 2025)

Low-temperature on-board hydrogen production using a novel hollow fibre-based packed bed reactor - Claire Leishman; Yuxiang Liu; Muhammad Akmal Bin Mohd Faisal; Kang Li; Francisco R. García-García (Chemical Engineering Journal, 2025)

Utilization of duckweed in phytomining of gold mine tailing and its potential to produce gold nanoparticle - Rizki Maulana Yusuf; Muhammad Alhas Finaldin; Wahyuni Eka Putri; Aurora Karina Chandra; Akmal Jihad; Yuliati Herbani; Awalina Satya; Evi Susanti; Hamim Hamim (Environmental Science and Pollution Research, 2025)

OhmNet: Advanced neural network-based viscosity prediction of sauces for efficient Ohmic heating processing - Tasmiyah Javed; Muhammad Akmal; Timofei Breikin; Caroline Millman; Hongwei Zhang (Innovative Food Science & Emerging Technologies, 2025)

Novel sequential ozonolysis-hydrolysis treatments for microcrystalline cellulose synthesis from oil palm empty fruit bunch - Pavitra Thevi Arnandan; Wan Nor Nadyaini Wan Omar; Zhahidah Husna Hassan; Muhammad Sufri Abd Muhaimin; Danish Akmal Jihat@Ahmad; Makam Mba Michele Raissa; Amnani Shamjuddin; Ken-Lin Chang; Nor Aishah Saidina Amin (Biomass and Bioenergy, 2025)

Relationship between perceived maneuverability and compensatory eye movements under systematically varied time constants of ride-on machinery - Muhammad Akmal Mohammed Zaffir; Daisuke Sakai; Yuki Sato; Takahiro Wada (Experimental Brain Research, 2025)

Resistance development, cross-resistance, and inheritance patterns in clothianidin and triazophos resistant strains of Oxycarenus hyalinipennis - Rabia Saeed; Naeem Abbas; Muhammad Akmal; Jam Nazir Ahmad (Crop Protection, 2025)

Advances in Antibiotic Biodegradation: Emerging Strategies and Challenges in Mitigating Environmental Contamination and Resistance - Ibnu Maulana Hidayatullah; Soen Steven; Adi Kusmayadi; Iftita Rahmatika; Muhammad Reski; Ramaraj Boopathy; Muhamad Akmal Alfatan; Putri Wilhelmina Gusanti Purba (Current Pollution Reports, 2025)

A novel active packaging film based on polyvinyl alcohol/bajakah tampala (Spatholobus littoralis hassk) extract: Enhancing mechanical, UV protection, thermal stability, antimicrobial, and barrier properties - Kadriadi; Dieter Rahmadiawan; Hairul Abral; Ilhamdi; Muhammad Ivan; Akmal; Dian Handayani; Laila Rezki Septria Ningrum; Rahmi Syarifah Masri; Bernadeta Ayu Widyaningrum; Mohamad Haafiz Mohamad Kassim; Melbi Mahardika (Food Bioscience, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

Morphological characteristics and phylogenetic analysis reveal Punctulariopsis fissurata sp. nov. (Punctulariaceae, Basidiomycota) from Yunnan, China - Akmal Muhammad; Minglan Chen; Wen Li; ChangLin Zhao (New Zealand Journal of Botany, 2025)
A new wood‐inhabiting fungal species, Punctulariopsis fissurata , is proposed based on morphological description and molecular verification. The species is characterised by the resupinate basidiomata with a pinkish buff salmon hymenial surface, a monomitic system with the generative hyphae bearing clamp connections and the presence of dendrohyphidia with broadly ellipsoid basidiospores measuring 13–15.5 × 8.5–11.5 µm. Phylogenetic analysis of the combined nrDNA‐ITS and LSU gene sequences verified that P. fissurata formed an independent lineage sister to P. efibulata with strong statistical support. A full description, illustrations and phylogenetic analysis results of the new species are provided.

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Pathology of an unusual outbreak of fatal disease associated with mycobacterial and Pseudomonas aeruginosa infections and intracytoplasmic inclusion bodies in juvenile spectacled caimans (Caiman crocodilus) - Sufiah U.N.K. Azlin; Nurul F. Muhammad Husairy; Charisha Fraser; Nurul I.U. Zahli; Mohd N. Akmal; Annas Salleh (Journal of Comparative Pathology, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

The potential of hydrolyzed chicken feather meal as a partial replacement for fish meal and its effects on the growth and health status of African catfish (Clarias gariepinus) fingerlings - Nik Nur Akmal ‘Aliah Abdul Rashid; Zulhisyam Abdul Kari; Parashuram Kallem; Suniza Anis Mohamad Sukri; Syed Muhammad Al-Amsyar; Noor Khalidah Abdul Hamid; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Martina Irwan Khoo; Krishnakumar Velayudhannair; Ajay Guru (Aquaculture International, 2025)

HIV-1 Nef Gene Characterization and Subtype Analysis in Pakistan: A Molecular Docking Approach with Mastoparan-L Peptide - Akmal Zubair; Muhammad Ali; Naseem Akhtar (International Journal of Peptide Research and Therapeutics, 2025)

PolarBytes: Advancing polar research with a centralized open-source data sharing platform - Nur Haznirah Hazman; Rohaizaazira Mohd Zawawi; Ainin Sofia Jusoh; Muhammad Akmal Remli; Marieanne Christie Leong; Mohd Saberi Mohamad; Sarahani Harun (Environmental Modelling & Software, 2025)

Clinical trials and recent progress in HIV vaccine development - Akmal Zubair; Bushra Bibi; Faiza Habib; Arooba Sujan; Muhammad Ali (Functional & Integrative Genomics, 2024)

Remediation of benzo[α]pyrene contaminated soil using iron naturally bearing in tropical soil: A new frontier in catalyst-free in soil remediation - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Chemosphere, 2024)

Soil remediation and nano-biosilica: a potential combination to improve the environmental quality of brackishwater aquaculture ponds affected by acid sulfate soils - Tarunamulia Tarunamulia; Akhmad Mustafa; Mudian Paena; Akmal Akmal; Mohammad Syachuddin; Kamariah Kamariah; Erna Ratnawati; Muhammad Ilman (Environmental Science and Pollution Research, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

Advanced oxidation of polycyclic aromatic hydrocarbons in tropical soil: Self-catalytic utilization of natural iron contents in an oxygenation reactor supported with persulfate - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Science of The Total Environment, 2024)

Energy and social factor decomposition to identify drivers impeding sustainable environmental transition in emerging countries: SDGs-2030 progress assessment using LMDI analysis - Qi Gao; Nida Raza; Dandan Sun; Muhammad Akmal; Faiz Nayab (Environmental Science and Pollution Research, 2024)

Harnessing the power of bacterial laccases for xenobiotic degradation in water: A 10-year overview - Mujeeb ur Rahman; Muhammad Wajid Ullah; Junaid Ali Shah; Sivasamy Sethupathy; Hazart Bilal; Sidikov Akmal Abdikakharovich; Afaq Ullah Khan; Khalid Ali Khan; Noureddine Elboughdiri; Daochen Zhu (Science of The Total Environment, 2024)

Tropical soil remediation from pyrene: Release the power of natural iron content in soil for the efficient oxidant's activation - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Khalid A. Alamry; Mahmoud A. Hussein (Journal of Environmental Management, 2024)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Assessing Household’s Municipal Waste Segregation Intentions in Metropolitan Cities of Pakistan: A Structural Equation Modeling Approach - Tanzila Akmal; Faisal Jamil; Muhammad Haseeb Raza; Cosimo Magazzino; Babar Hussain (Environmental Monitoring and Assessment, 2023)
There is a growing concern about inappropriate waste disposal and its negative impact on human health and the environment. The objective of this study is to understand household waste segregation intention considering psychological, institutional, and situational factors simultaneously. Insights into the motivations of household waste segregation drivers may assist in a better knowledge of how to pursue the most efficient and effective initiatives. For this purpose, data from a representative sample comprising 849 households is obtained from the twin cities of Islamabad and Rawalpindi (Pakistan). The empirical analysis employs a Structural Equation Modeling (SEM) approach, showing that policy instruments have significant direct and indirect impacts on households’ segregation intentions. The results highlight that government policy instruments strengthen personal and perceived norms for waste segregation intentions, resulting in an external intervention that would encourage intrinsic motivation. Therefore, policy actions become the main entry point for initiating waste segregation behavior. Public policy must continue to emphasize waste segregation since it may help resource recovery. This is imperative because the environment is a shared resource, and its conservation increases social welfare.

Resistance and genomic characterization of a plasmid pkh2101 harbouring erm (B) isolated from emerging fish pathogen Lactococcus garvieae serotype II in Japan - Muhammad Akmal; Mami Akatsuka; Issei Nishiki; Terutoyo Yoshida (Journal of Fish Diseases, 2023)
The emergence of antibiotic‐resistant pathogenic strains of Lactococcus garvieae serotype II isolated from fish in Japan has become a growing concern in recent years. The data on drug susceptibility and its associated resistance mechanism are limited. Therefore, the present study was conducted to determine the minimum inhibitory concentrations (MICs) of chemotherapeutic agents against 98 pathogenic strains of emerging Lactococcus garvieae serotype II isolated from fish from six different prefectures in Japan from 2018 to 2021. The tested strains were resistant to erythromycin, lincomycin and tiamulin. PCR amplification revealed the presence of erm (B) in all erythromycin‐resistant strains, while a conjugation experiment confirmed that these strains carried erm (B) that could be transferred to recipient Enterococcus faecalis OG1RF with frequencies from 10 −4 to 10 −6 per donor cells. Nucleotide sequencing of the representative isolated plasmid pkh2101 from an erythromycin‐resistant strain showed that it was a 26,850 bp molecule with an average GC content of 33.49%, comprising 31 CDSs, 13 of which remained without any functional annotation. Comparative genomic analysis suggested that pkh2101 shared the highest similarity (97.57% identity) with the plasmid pAMbeta1, which was previously isolated clinically from Enterococcus faecalis DS‐5. This study provides potential evidence that the plasmid harbouring erm (B) could be a source of antibiotic resistance transmission in emerging L. garvieae infection in aquaculture.

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

Oil palm yield prediction across blocks from multi-source data using machine learning and deep learning - Yuhao Ang; Helmi Zulhaidi Mohd Shafri; Yang Ping Lee; Shahrul Azman Bakar; Haryati Abidin; Mohd Umar Ubaydah Mohd Junaidi; Shaiful Jahari Hashim; Nik Norasma Che’Ya; Mohd Roshdi Hassan; Hwee San Lim; Rosni Abdullah; Yusri Yusup; et al. (Earth Science Informatics, 2022)

Complete genome sequence of a novel lytic bacteriophage, PLG-II, specific for Lactococcus garvieae serotype II strains that are pathogenic to fish - Muhammad Akmal; Issei Nishiki; Nikita Zrelovs; Terutoyo Yoshida (Archives of Virology, 2022)

Identification of novel biofilm genes in avian pathogenic Escherichia coli by Tn5 transposon mutant library - Jiangang Hu; Yi Gu; Huiqi Lu; Muhammad Akmal Raheem; Fangheng Yu; Xiangpeng Niu; Jiakun Zuo; Huifang Yin; Cuiqin Huang; Xiangjun Song; Jian Tu; Wen Zhou; et al. (World Journal of Microbiology and Biotechnology, 2022)

Plastics in the environment as potential threat to life: an overview - Imania Ghaffar; Muhammad Rashid; Muhammad Akmal; Ali Hussain (Environmental Science and Pollution Research, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Addressing the unfulfilled codex standard for honey for stingless bee honey through lyophilization - Chin-Hong Yong; Syahidah Akmal Muhammad; Widad Fadhullah; Hasnuri Mat Hassan; Ainolsyakira Mohd Rodhi; Mohd Zulkifli Mustafa; Simon D. Kelly (Isotopes in Environmental and Health Studies, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Comparison of Early Succession and Scleractinian Recruitment Between Artificial Live Rocks and Terracotta Tiles - Yusof Muhammad Hamizan; Shahbudin Saad; Mohd Azrul Naim; Mohd Fikri Akmal Khodzori; Muhammad Faiz Mohd Hanapiah (Ocean Science Journal, 2021)

Correction to: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

RETRACTED ARTICLE: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Potential Risk and Occupational Exposure of Pesticides Among Rice Farmers of a Village Located in Northern Peninsular of Malaysia - Nur Anis Ahmad; Ali Salehabadi; Syahidah Akmal Muhammad; Mardiana Idayu Ahmad (Exposure and Health, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Impact of biochar with different organic materials on carbon fractions, aggregate size distribution, and associated polysaccharides and soil moisture retention in an arid soil - Munir Abbas; Shahzada Sohail Ijaz; Muhammad Ansar; Qaiser Hussain; Asma Hassan; Muhammad Akmal; Muhammad Tahir; Muhammad Iqbal; Kashif Bashir; Sana-ur-Rehman (Arabian Journal of Geosciences, 2019)

Diversity and Abundance of Scleractinian Corals in the East Coast of Peninsular Malaysia: A Case Study of Redang and Tioman Islands - Khodzori Fikri Akmal; Saad Shahbudin; Mohd Hanapiah Muhammad Faiz; Yusof Muhammad Hamizan (Ocean Science Journal, 2019)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Carbon mineralization in subtropical dryland soil amended with different biochar sources - Sehar Sultan; Khalid Saifullah Khan; Muhammad Akmal; Zammurad Iqbal Ahmed; Qaiser Hussain; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Identifying a Gene Knockout Strategy Using a Hybrid of Simple Constrained Artificial Bee Colony Algorithm and Flux Balance Analysis to Enhance the Production of Succinate and Lactate in Escherichia Coli - Mei Kie Hon; Mohd Saberi Mohamad; Abdul Hakim Mohamed Salleh; Yee Wen Choon; Kauthar Mohd Daud; Muhammad Akmal Remli; Mohd Arfian Ismail; Sigeru Omatu; Richard O. Sinnott; Juan Manuel Corchado (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

Bioactive constituents from Croton sparsiflorus Morong - Durre Shahwar; Naeem Ahmad; Asma Yasmeen; Muhammad Akmal Khan; Sami Ullah; Rahman Atta-ur (Natural Product Research, 2015)

A simple method for simultaneous determination of some organic liquids in in-process materials and effluents produced in the manufacture of amoxicillin and ampicillin - Mohammad S Iqbal; Muhammad A Akmal (Environmental Monitoring and Assessment, 2009)